The anaphase promoting complex promotes NHEJ repair through stabilizing Ku80 at DNA damage sites. Issue 9 (3rd May 2018) - Ma, Chengxian; Ha, Kyungsoo; Kim, Min-su; Noh, Young-Woock; Lin, Han; Tang, Lichun; Zhu, Qing; Zhang, Dan; Chen, Huan; Han, Suxia; Zhang, Pumin
ABSTRACT: Double-strand breaks (DSBs) are repaired through two major pathways, homology-directed recombination (HDR) and non-homologous end joining (NHEJ). The choice between these two pathways is largely influenced by cell cycle phases. HDR can occur only in S/G2 when sister chromatid can provide homologous templates, whereas NHEJ can take place in all phases of the cell cycle except mitosis. Central to NHEJ repair is the Ku70/80 heterodimer which forms a ring structure that binds DSB ends and serves as a platform to recruit factors involved in NHEJ. Upon completion of NHEJ repair, DNA double strand-encircling Ku dimers have to be removed. The removal depends on ubiquitylation and proteasomal degradation of Ku80 by the ubiquitin E3 ligases RNF8. Here we report that RNF8 is a substrate of APC Cdh1 and the latter keeps RNF8 level in check at DSBs to prevent premature turnover of Ku80.